Perbandingan Penerapan Nilai-nilai Akhlaq dan Etika dalam Pendidikan Agama Islam di Pondok Pesantren Ta'mirul Islam Tahun Pelajaran 2014/2015 - Muttaqin, Muhammad Zainal; , Drs. Zaenal Abidin, M.Pd; , Drs. Arif Wibowo, M.Ag (2015)
Muhammad Zainal Muttaqin, G000130168, Islamic Religious Education Program (MT) Faculty of Islamic Studies, University of Muhammadiyah Surakarta. In teaching moral values ​​and ethics in Islamic education on students, Ta'mirul Islamic boarding school experience many challenges that arise due to the influence of Western culture internalization. As a result, many students who have not been able to explore the moral values ​​and ethics properly. So it appears naughtiness students that should not be done at the cottage. The delinquency such as: stealing, smoking, going out, out of the hut without permission, skipping school, no discipline in the school entrance and entered the mosque, fighting, making fun of the teachers, and others. Of the problem, the necessary teaching and nurturing the right in instilling moral values ​​and ethics to the students. Based on the background of the problem can be formulated on the application of comparative moral values ​​and ethics in Islamic religious education in Ta'mirul Islamic boarding school in the academic year 2014/2015. The aim of this study was to describe the comparison of the application of moral values ​​and ethics in Islamic Education in Ta'mirul Islamic boarding school in the academic year 2014/2015. This type of research is classified as field research (field research) .This method of data collection used is documentation, observation and interviews. As for analyzing the results of this research approach was used qualitative descriptive analysis of five activities, namely collecting data and all data from various sources (interviews, observation, and documentation), reduce the data, and then filtered in accordance with the theory and formulation of the problem, the data is presented in narrative form, and conclusion. These results indicate that: Boarding Ta'mirul Islam more apply moral values ​​rather than applying ethical values ​​in Islamic education in the daily life of students at the cottage. Moral values ​​applied refer to the curriculum MONE and MORA plus curriculum curriculum lembaga.Adapun aspect of moral values ​​that apply to students are: the rules governing human relationships with Allah¬ (in terms of patterns of behavior and attitude to God, among others covering aspects of the values ​​of faith, worship mahḍah, and morality), the relationship between humans (in terms of patterns of behavior to fellow human beings), man's relationship with nature as a whole (in terms of the natural behavior patterns). While ethics is applied is the aspect of ethical values ​​that include social etiquette, ethics neighbors, ethics behave politely to the parents as saying politely to the parents, the ethics of eating with the right hand, ethics sneezing in front of the crowd, ethics sit, ethics shake hands, sleep ethics, ethics undressed. .